PENGARUH MENGUNYAH BUAH BELIMBING MANIS (Avverhoa carambola L) TERHADAP PLAK SKOR PADA SISWA KELAS VII SMPN 11 BANJARBARU - Siti Sabátul habibah; Fitri Imroatus Sholikhah; Sri Nuryati (JURNAL TERAPIS GIGI DAN MULUT, 2020)
Plaque control is an effort to remove and prevent plaque buildup on the tooth surface. These efforts can be done mechanically or chemically. Based on a preliminary study conducted by researchers at SMP Negeri 11 Banjarbaru from 5 students, 3 people with a moderate score plaque and 2 poor people. Chewing sweet star fruit (Avverhoa carambola L) is a non-climatic fruit that has a thin skin, has a sweet and refreshing taste, also has antioxidant and antibacterial benefits. This study aims to determine the effect of chewing Sweet Starfruit (Averrhoa carambola L) on the plaque scores in grade VII students of SMP Negeri 11 Banjarbaru. This type of research is quasi-experimental, with a One Group Pretest-Postest design. This research was conducted at SMPN 11 Banjarbaru. This study involved 56 samples. Data were collected using a PHP measuring instrument before and after chewing Sweet Starfruit (Avverhoa carambola L). From the results of statistical analysis with the Paired t-test, it is found that the Mean is 1.3357, with the known p value (probability value) of the test shows p = 0.0000, so it is smaller than α 0.05 or (p = 0.000 <α 0,05), in other words Ho is rejected and accepted, that is, there is an effect of chewing sweet starfruit on the score plaque in grade VII students at SMPN 11 Banjarbaru, South Kalimantan. Chewing sweet starfruit is effective in reducing plaque score, because the results of the study show that there is a significant difference between before chewing sweet star fruit (avverhoa carambola L) and after chewing sweet star fruit (avverhoa carambola L), it is hoped that dental health workers can provide counseling about maintenance of oral health includes good and bad food for oral health. Keywords: Chewing Sweet Starfruit, Plaque Score